PENATALAKSANAAN TERAPI OKUPASI PADA AN.W DENGAN HALUSINASI PENDENGARAN DI RSJ SOEROJO MAGELANG - Cicilia Aditya Melinda; Ita Apriliyani (Jurnal Cakrawala Ilmiah, 2023)
Hallucinations are perceptual disorders in which the patient expresses something that is not actually happening. As a result of untreated hallucinations, unwanted things can also appear, such as hallucinations that instruct the patient to do things such as kill himself or injure others. One of the treatments for sensory perception disorder patients: auditory hallucinations is by means of occupational therapy (drawing). The general objective of this scientific work is to provide mental nursing care to An.W by applying occupational therapy: drawing to control auditory hallucinations at Soerojo Hospital, Magelang. The research design used a case study with a nursing care approach. The sample in this study was An W, a mental patient with a medical diagnosis of Schizophrenia at Soerojo Hospital Magelang. Based on the results of observations of therapy that has been carried out for 3 days in the application of occupational therapy, it shows that occupational therapy has an effect on changes in symptoms in patients with auditory hallucinations. In conclusion, occupational therapy for free time activities such as drawing, coloring, sweeping, making the bed and playing together is done 1-2 times a day for 15-25 minutes can minimize the patient's interaction with his own world and can control the symptoms of hallucinations.